Analisis Kesesuian Gambar Dan Penggunaan Kata Dan Tanda Baca Pada Media Spanduk Berbasis Digital - Abdul Sakti; B. Syukroni Baso (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research aims to analyze the suitability of images and the use of words and punctuation on digital media. The research method used was observation of a digital banner displaying an image of a chair with the words "UP TO 50% OFF" and an image of a meatball bowl with a discount offer of up to 50% as well as the information "Weekend Special Delicious Food Menu." The research results showed that the use of an image of a chair and the meatball bowl effectively supports the message you want to convey. The color design chosen, such as the dominance of orange on the meatball banner, gives an impression that matches the characteristics of the food offered. The use of the word "delicious" in the text "Weekend Special Delicious Food Menu" provides added value in arousing the reader's appetite. In addition, the arrow pointing to the text "Home Delivery" on the meatball banner helps convey delivery service information clearly. The "Order Now" instruction with the addition of a telephone number and website address provides clear guidance to consumers for placing an order. The use of punctuation, such as commas and periods, on the banner effectively separates the information and improves readability. Punctuation helps readers clearly understand any information presented, such as phone numbers and website addresses.